The Relationship Between Adolescent Girls' Knowledge And Attitudes and The Prevalence of Vaginal Discharge - Musfiroh, Sri (Jurnal Medisci, 2025)
Background. Vaginal discharge can be physiological (normal) or pathological (abnormal). Physiological vaginal discharge occurs before or after menstruation, without odor or itching. Pathological vaginal discharge is characterized by odorous, viscous, and itchy or burning fluids, triggered by pH imbalances, infections, or unhealthy habits such as the use of dirty water or the infrequent change of sanitary napkins Aims. This study aims to examine the relationship between knowledge and attitudes of adolescent girls and the incidence of vaginal discharge at SMAN 1 Rajagaluh, Majalengka Regency, to support more effective reproductive health education efforts. Methods. This study uses a quantitative design with a cross-sectional approach to examine the relationship between the knowledge and attitudes of adolescent girls and the incidence of vaginal discharge at SMAN 1 Rajagaluh, Majalengka Regency. Measurements of independent (knowledge and attitude) and dependent (vaginal discharge events) variables were carried out simultaneously at one time without follow-up. Conclusion. Adolescent girls with a positive attitude had a 12.67 times greater chance of not experiencing vaginal discharge than those who behaved negatively, Implementation. Controlling for disruptive variables such as age and hygiene habits